(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
Surfaces with metal oxide nanostructures are becoming more popular for use in sensors, detectors, energy harvesting cells, and batteries. However, the limitations of conventional fabrication techniques impede the widespread and productive application of such surfaces. The majority of techniques for producing metal oxide nanostructures are pricey, complicated, hazardous to the environment, or restricted to a few particular material types. It is crucial to develop an easy way to make metal oxide nanostructures that can get beyond all of these limitations. This work used hot deionized water methods to prepare copper oxide nanostructures through thermal oxidation. A pure copper plate with two different surface roughness (0 grit and 80 grit) was subjected to four separate treatments with hot DI water at 100°C (0, 1, 5, 9 hours). The surface morphology of the nanostructures was studied using atomic force microscopy, and it was shown that the Root Mean Square roughness increased with treatment time. The semiconductor’s characteristics were assessed using Hall effect measurements, and all test samples displayed p-type conductivity. UV-Vis spectroscopy was used to determine the optical properties; samples with 0 grit show an increase in UV absorption with longer treatment times, whereas samples with 80 grit show a decrease in UV absorption with longer treatment times.